THE STUDENTS' PERCEPTIONS ABOUT THE USE OF INNTERACTIVE VIDEO: INTERACTIVE VIDEO - Dandi, Dandi Putra Suherman; Bunga Putri Dewi (SEAMEO SEAMOLEC, 2024)
Interactive video using H5P is a feature that can be freely used by Moodle users; however, as a phenomenon in the field, only a small number use it. Based on monitoring through the system at one university, only 0.085% of 10,593 students used H5P in course sessions. In this case, it means that the implementation of the H5P-based interactive video was not carried out well; on the other hand, evaluation is needed. This research involves the perspective of students who have used H5P. This research activity uses a quantitative approach carried out at Padang State University. The research sample involves students taking computer-based learning courses. Students were given a questionnaire to see their perspective on using H5P as interactive content in the learning process. This data was analysed using data analysis techniques. From the results obtained, according to students' views, H5P as an interactive learning media to support the Padang State University LMS system has a positive impact. By looking at the capabilities and efficiency of the existing H5P, of course, this is applied objectively. Hence, to maximise the use of H5P content, students, lecturers, and universities must consider the problems faced, such as networks, devices, technical use of H5P, work orders, navigation, and time, as concluded in this research.